2009
DOI: 10.1103/physrevb.79.014110
|View full text |Cite
|
Sign up to set email alerts
|

Theory of phase spectroscopy in bimodal atomic force microscopy

Abstract: We develop a theoretical formalism to describe bimodal atomic force microscopy ͑AFM͒ experiments. The theory relates observables such as amplitudes and phase shifts to physical properties of the tip-surface interaction. The theory is compatible with point-mass and continuous models of the cantilever-tip system. We explain the ability of the bimodal AFM to map compositional variations under the influence of very small conservative forces. This is achieved by representing the dependence of the phase shift or amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
96
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 49 publications
1
96
0
Order By: Relevance
“…Conventional theory that relates phase contrast, a key observable in dAFM, to tip-sample dissipation assumes that the cantilever motion can be described by using a single spatial eigenmode with, perhaps, higher harmonic temporal content. In ambient environments, high quality factors eliminate the energy propagation between eigenmodes, even in the case of bimodal (2-frequency) excitation (31,32). We have shown that this assumption breaks down when soft cantilevers are used in liquids where the dynamics are naturally multimodal due to the momentary excitation of higher eigenmodes.…”
Section: Resultsmentioning
confidence: 95%
“…Conventional theory that relates phase contrast, a key observable in dAFM, to tip-sample dissipation assumes that the cantilever motion can be described by using a single spatial eigenmode with, perhaps, higher harmonic temporal content. In ambient environments, high quality factors eliminate the energy propagation between eigenmodes, even in the case of bimodal (2-frequency) excitation (31,32). We have shown that this assumption breaks down when soft cantilevers are used in liquids where the dynamics are naturally multimodal due to the momentary excitation of higher eigenmodes.…”
Section: Resultsmentioning
confidence: 95%
“…This expression is equivalent to those derived by others 23,24 but its interpretation here leads to key results relating to energy transfer and phase contrast as discussed below. In standard AM AFM the fundamental phase shift / 1 might lie above or below 90 in what defines two distinct force regimes, 25 i.e., the attractive and the repulsive regimes, where the average tip-sample force F AV is attractive or repulsive, respectively.…”
mentioning
confidence: 72%
“…To study the effect of energy dissipation in the bimodal phase contrast, in addition the above conservative force, we introduce the following non-conservative interaction [47]: (7) The power dissipated in the sample for each mode is calculated by [47] (8) Figure 3a,b show the dependence of versus A 1 /A 01 when the tip-sample interaction includes non-conservative interactions. The phase shift increases by reducing the A 1 /A 01 -ratio until a maximum is reached for ratios below 0.2.…”
Section: Materials and Cantilever-tip Parametersmentioning
confidence: 99%